Proceedings of the 20th International ACM SIGACCESS Conference on Computers and Accessibility 2018
DOI: 10.1145/3234695.3236349
|View full text |Cite
|
Sign up to set email alerts
|

Interactiles

Abstract: The absence of tactile cues such as keys and buttons makes touchscreens difficult to navigate for people with visual impairments. Increasing tactile feedback and tangible interaction on touchscreens can improve their accessibility. However, prior solutions have either required hardware customization or provided limited functionality with static overlays. Prior investigation of tactile solutions for large touchscreens also may not address the challenges on mobile devices. We therefore present Interactiles, a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Research works on 3-D-printed models with haptic interaction have also been reported. Reference [18] uses Android phones to enhance the tactile interaction on phones' touchscreens. This is achieved by the use of an application that maps the interactions with a previously printed hardware.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research works on 3-D-printed models with haptic interaction have also been reported. Reference [18] uses Android phones to enhance the tactile interaction on phones' touchscreens. This is achieved by the use of an application that maps the interactions with a previously printed hardware.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, while the accessibility of photographs for BLV was largely investigated in terms of web accessibility [21,38], only three out of 33 papers aimed to support photographs using touchscreen devices in particular. In addition, as touchscreen devices themselves have accessibility issues for people with visual impairments, requiring accurate hand-eye coordination [26], four papers focused on improving the accessibility of the touchscreen-based interface itself such as soft buttons [39][40][41] and gestures [42].…”
Section: Supported Image Typesmentioning
confidence: 99%
“…For example, Gotzelmann et al [23] used a 3D-printed tactile map. Zhang et al [41] also made user interface elements (e.g., buttons, sliders) with a 3D printer to improve the accessibility of touchscreen-based interfaces in general by replacing virtual elements on a touchscreen with physical ones. Moreover, Hausberger et al [56] proposed an interesting approach using kinesthetic feedback along with frictions.…”
Section: Interaction Typesmentioning
confidence: 99%
“…Over the last decade, numerous projects aimed at improving touchscreen interfaces, including understanding the performance of gestures [41], proposing new text input techniques [6,24,51,52], and leveraging Braille knowledge [4,58]. Other solutions took advantage of concurrent speech feedback [23], augmented touchscreens with physical interfaces [40,60,62] or haptic feedback [19,46]. Touchscreen devices have also been combined with computer vision-based solutions to create novel assistive technologies [26,27].…”
Section: Touchscreen Accessibilitymentioning
confidence: 99%